Back pain and scoliosis in children: When to image, what to consider. Issue 5 (October 2017) - Calloni, Sonia F; Huisman, Thierry AGM; Poretti, Andrea; Soares, Bruno P
Back pain and scoliosis in children most commonly present as benign and self-limited entities. However, persistent back pain and/or progressive scoliosis should always be taken seriously in children. Dedicated diagnostic work-up should exclude etiologies that may result in significant morbidity. Clinical evaluation and management require a comprehensive history and physical and neurological examination. A correct imaging approach is important to define a clear diagnosis and should be reserved for children with persistent symptoms or concerning clinical and laboratory findings. This article reviews the role of different imaging techniques in the diagnostic approach to back pain and scoliosis, and offers a comprehensive review of the main imaging findings associated with common and uncommon causes of back pain and scoliosis in the pediatric population.